Visual programming environment - Kuo, Wen Siang. (2009)
Recent advancement in the technology of graphics-related devices have made it feasible to use pictures to communicate with computers, and to use computer graphics as a medium to facilitate programming. As a result visual programming applications have gained momentum in recent years.